Rekonstruksi Tari Bedhaya Endhol-endhol di Keraton Kasunanan Surakarta Hadiningrat - Kezia Putri Herawati; Nanik Sri Prihatini (LP2M ISBI Bandung, 2018)
ABSTRACTThe Bedhaya Endhol-endhol dance was created by Paku Buwono X and performed exclusively by the king’s daughters. After his death, the dance was no longer performed and its form was no longer known. The goal of this research is to reveal the process of reconstruction of the Bedhaya Endhol-endhol dance, as carried out by Gusti Kanjeng Ratu Wandansari, and to describe the form of the dance. The research method used is a qualitative method with an ethnochoreological approach. The results of the research show the process of reconstruction, including the concept and the process of unearthing the music, or gending, and the dance movements. The arrangement process involved the interpretation of all the different components making up the Bedhaya Endhol-endhol dance, in order to create a new form of bedhaya dance that is childlike (mbocahi). The new form of Endhol-endhol resulted from its reconstruction shows that Gusti Kanjeng Ratu Wandansari has used her authority to restore the dance that had formerly disappeared. Keywords: Bedhaya Endhol-endhol dance, reconstruction, authority, Gusti Kanjeng Ratu Wandansari.ABSTRAKTari Bedhaya Endhol-endhol yang khusus ditarikan oleh putri-putri raja diciptakan oleh Raja Paku Buwono X. Sejak beliau wafat tari ini tidak pernah dipentaskan dan bentuknya pun tidak dikenali lagi. Penelitian ini bertujuan mengungkap proses rekonstruksi tari Bedhaya Endhol-endhol dan mendiskripsikan wujudnya yang telah dilakukan oleh Gusti Kanjeng Ratu Wandansari. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan etnokoreologi. Hasil penelitian meliputi proses rekonstruksi mencakup konsepnya, proses penggalian meliputi gending dan gerak tarinya. Pada proses penataan dilakukan interpertasi mengenai semua komponen yang membentuk tari Bedhaya Endhol-endhol untuk mewujudkan tari bedhaya yang mbocahi. Wujud tari Bedhaya Endhol-endhol hasil rekonstruksi menunjukkan bahwa dengan otoritasnya Gusti Kanjeng Ratu Wandansari telah mengembalikan tari yang sempat hilang.Kata kunci: Tari Bedhaya Endhol-endhol, rekonstruksi, otoritas, Gusti Kanjeng Ratu Wandansari